Dimensional Optimization of TiO2 Nanodisk Photonic Crystals on Lead Iodide (MAPbI3) Perovskite Solar Cells by Using FDTD Simulations - Lilik Hasanah; Adryan Ashidiq; Roer Eka Pawinanto; Budi Mulyanti; Chandra Wulandari; Wiendartun; Ahmad Rifqi Md. Zain (Applied Sciences, 2021)
Perovskite solar cells (PSC) are currently exhibiting reproducible high efficiency, low-cost manufacturing, and scalable electron transport layers (ETL), which are becoming increasingly important. The application of photonic crystals (PC) on solar cells has been proven to enhance light harvesting and lead solar cells to adjust the propagation and distribution of photons. In this paper, the optimization of a two-dimensional nanodisk PC introduced in ETL with an organic-inorganic lead-iodide perovskite (methylammonium lead-iodide, MAPbI3) as the absorber layer was studied. A finite-difference time-domain (FDTD) simulation was used to evaluate the optical performance of PSC with various lattice constants and a radius of nanodisk photonic crystals. According to the simulation, the optimum lattice constant and PC radius applied to ETL are 500 nm and 225 nm, respectively. This optimum design enhances PSC absorption performance by more than 94% of incident light.